RISK FACTORS AND CLINICAL MANIFESTATIONS OF LUNG MYCOBACTERIOSIS. SYSTEMATIC REVIEW - T.KH. AMIROVA; I.V. PETROV; L.V. RYZHOVA; F.S. PETROVA; L.V. PETROVA; A.A. ALMUKHAMETOV (Avicenna Tajik State Medical University, 2021)
The present study is a systematic review with a meta-analysis of risk factors for lung mycobacteriosis (LM) and diseases that influence the incidence, clinical manifestations and etiology of the infection under investigation. The authors made a selection of papers. The search for papers was carried out in English and Russian in the PubMed, Web of Science, Сochrane Library, eLibrary electronic databases with the analysis of references from the articles found. Articles published from 2000 to 2020 were selected. The following results are obtained. Regarding smoking: with the two gradations of the factor (the patient smokes or not), the incidence of LM in smokers varied from 13.8±0.03% to 71.2±0.06%. Regarding tuberculosis: the incidence of LM and tuberculosis ranged from 6.7±0.01% to 17.6±0.02%. Regarding chronic obstructive pulmonary disease (COPD): the incidence of LM in patients with COPD was determined on average at 11.2±0.01%. Regarding bronchiectasis: the incidence of bronchiectasis in patients with LM is 30.1±0.02%. Regarding diabetes mellitus: the frequency of patients with LM and diabetes mellitus in one study group was 6.7±0.01%, and in the other - 17.6±0.02%. Regarding malignancies: the frequency of such patients was determined from 17.1±0.04% to 50.0±0.07% of cases. Regarding HIV infection and LM: the incidence of detected LM in patients with HIV was determined on average at the level of 8.9±0.01%. Regarding cough in LM: the frequency of patients with this symptom in the first group was 46.2±0.07%, in the second group - 88.9±0.02%. Regarding hemoptysis in LM: the frequency of patients with this symptom ranged from 3.8±0.03% to 30.1±0.02%. X-ray manifestations of lesions in LM occurred with a frequency of 42.3±0.04% to 100%. The most significant role in etiology belongs to non-tuberculous mycobacteria species, such as slow-growing M. avium complex, and fast-growing M. abscessus complex, M. chelonae, M. fortuitum.